Household valuation of energy development in amenity‐rich regions. (16th October 2019) - Stephens, Heather M.; Weinstein, Amanda L.
Abstract: The juxtaposition of oil and gas wells against the Rocky Mountains on Colorado's Front Range provides a picture of the complicated interaction between Colorado's natural resources above and below ground. As hydraulic fracturing has increased oil and gas development—bringing jobs and money to an already highly sought after amenity‐rich area—it has also increased concerns about the impact on natural amenities, such as water quality and mountain views. Using data on housing sales between 2006 and 2014, we estimate how shale development is capitalized into housing prices in a booming market when households are in close proximity to other natural amenities. We find that shale development negatively impacts house prices, more so for houses with private water and houses that are closer to the mountains, but that competition for land along the Front Range has driven up house prices overall in the region. Our results also suggest the policy responses to shale development may differ for growing, amenity‐rich regions.